Safeguarding Private Value in Public Spaces: The Neoliberalization of Public Service Work in New York City's Parks - Krinsky, John (Social justice, 2011)
The article looks at economic and sociological aspects of urban public parks, as of 2011, focusing on New York City. The authors present an analysis in which they link ideological shifts in the conceptualization of the value of parks with neoliberal changes in the financing and employment practices involved in park maintenance. They recount the shift of park maintenance work from unionized public-sector workers to lower-paid workers including contract workers, offenders fulfilling community service requirements, and welfare recipients. Topics include privatization, private park conservancy organizations, and the effect of parks on nearby real-estate values.